The influence of Islamic banking products’ features on customer satisfaction in Nigeria - Abdullahi Baba, Bashir (2021)
Islamic banking is important in today’s competitive banking markets. Research in Islamic banking worldwide is largely focused on how distinct is Islamic banking from the conventional banking. Attaining customer satisfaction becomes the target of every organisation but the way to achieving customer satisfaction seems too difficult or not possible as a result of many overarching factors. This research investigates the effect of Islamic bank products features on customer satisfaction using the Kano theory of customer satisfaction. The objectives of the study are to identify the Islamic banking products’ as they relate to customer satisfaction. To determine the level of customer satisfaction on Islamic banking products’ features, and to investigate the influence of the products’ features on customer satisfaction in Nigeria. Three research questions and four hypotheses were formulated to guide the study. The methodology employed was a quantitative approach using a questionnaire as an instrument for data collection. The target population for this study is the customers of Ja’iz bank Nigeria Plc the only Islamic bank in Nigeria. A convenient sampling method was adopted to draw the respondents from the customers of the Ja’iz bank Plc. in Northern Nigeria. Hence selfadministered